2001
DOI: 10.1046/j.1365-2109.2001.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed pigment type on flesh pigment deposition and colour in farmed Atlantic salmon, Salmo salar L.

Abstract: The characteristic pink colour of salmonid¯esh is a result of deposition of naturally occurring carotenoid pigments. Achieving successful pigmentation in farmed salmonids is a vital aspect of ®sh farming and commercial feed production. Currently commercial diets for farmed salmonids contain either or both of the synthetic pigments commercially available, astaxanthin and canthaxanthin. Atlantic salmon, Salmo salar L. ( = 220 g initial weight) were given feeds where the pigment source was astaxanthin only, canth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
4
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 25 publications
6
67
4
2
Order By: Relevance
“…In Atlantic salmon, SalmoFan was able to score an increase in colour when increasing proportions of canthaxanthin were added to the feed compared with astaxanthin (Buttle et al, 2001). In the same species, some interesting studies showed a significant linear correlation between the SalmoFan score and muscle astaxanthin concentration .…”
Section: Discussionmentioning
confidence: 74%
“…In Atlantic salmon, SalmoFan was able to score an increase in colour when increasing proportions of canthaxanthin were added to the feed compared with astaxanthin (Buttle et al, 2001). In the same species, some interesting studies showed a significant linear correlation between the SalmoFan score and muscle astaxanthin concentration .…”
Section: Discussionmentioning
confidence: 74%
“…It is widely used for measuring the colour of seafoods such as Atlantic salmon, 4 rainbow trout, 5 Arctic charr 6 and surimi products. 7 Although the Minolta colorimeter provides simple and fast colour measurements, it has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The Enteromorpha Improving shrimp quality through dietary incorporation of natural algal astaxanthin sample selected for the investigation is found to contain 120.78 ppm astaxanthin as reported from the present study region (Mitra et al, 2013;Banerjee et al, 2009;Chakraborty and Santra, 2008). Carotenoid, particularly astaxanthin content of feed is one of the major factors influencing the colour development in animals (Moretti et al, 2006) but at the same time scientific knowledge about several factors like dietary pigment source, their dosage level, feeding duration, dietary composition and magnitude of carotenoid esterification is also required to identify these interaction processes (Meyers and Latscha, 1997;Bjerkeng, 2000;Buttle et al, 2001;Gomes et al, 2002;White et al, 2002). The present study showed significantly different astaxanthin content of the farmed shrimp which are in agreement to the observations that crustaceans exhibit strong tendency towards selection of specific carotenoids at a specific rate for their metabolic absorption (Meyers and Latscha, 1997).…”
Section: Resultsmentioning
confidence: 99%